2021
DOI: 10.3390/vetsci8090180
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of SLA-1, SLA-2, and DQB1 Genetic Diversity in Locally-Adapted Kenyan Pigs and Their Wild Relatives, Warthogs

Abstract: Swine leukocyte antigen (SLA) plays a central role in controlling the immune response by discriminating self and foreign antigens and initiating an immune response. Studies on SLA polymorphism have demonstrated associations between SLA allelic variants, immune response, and disease resistance. The SLA polymorphism is due to host-pathogen co-evolution resulting in improved adaptation to diverse environments making SLA a crucial genomic region for comparative diversity studies. Although locally-adapted African p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…Some studies have shown that the SLA protein family is closely related to stress resistance; TP have good stress resistance, which is consistent with the results of this study [ 43 ]. The expression level of the SELENBP1 gene in the body is closely related to the duration of hypoxia and ischemia and is involved in myocardial hypoxia [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have shown that the SLA protein family is closely related to stress resistance; TP have good stress resistance, which is consistent with the results of this study [ 43 ]. The expression level of the SELENBP1 gene in the body is closely related to the duration of hypoxia and ischemia and is involved in myocardial hypoxia [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Total RNA was isolated from 10 porcine spleen samples (3 each for the high, medium and low dose groups, and one uninfected control). Total RNA was extracted from 10 mg of spleen tissue using a modified protocol described previously [ 155 ] that combines tissue lysis with TRIzol™ (Thermo Fisher Scientific, USA) and silica-column purification using the RNeasy® Mini Kit (Qiagen, Germany) with on-column DNase I treatment step (Thermo Fisher Scientific, USA). The pure RNA was eluted from the columns using 40 μl of nuclease-free water.…”
Section: Methodsmentioning
confidence: 99%